ANÁLISE DE TENDÊNCIAS ATUAIS DE PESQUISA SOBRE TAIPA DE PILÃO - Dotta, Natália; Yuba, Andrea Naguissa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The information about nonconventional building construction technologies is diverse and has many sources. The scientific data about low-tech building systems, such as rammed earth and other earth-based systems, are scarcer than conventional ones, and it is hard to provide a good quality literature review. The analysis of this information would contribute to understand and clarify the trends of the research fields. This work aims to identify the trends of research production about rammed earth in the last 5 years (2013-2018). A bibliometric study was carried out, performing a systematic literature review of SCOPUS Database papers. There are very clear themes extensively studied and some gaps among them. These data can help to define new frontiers to explore about the theme.